2022
DOI: 10.1177/11786302221076707
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Cancer in a Community Exposed to Per- and Poly-Fluoroalkyl Substances

Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) emissions from a plastic coating industrial source in southern New Hampshire (NH) have contaminated at least 65 square miles of drinking water. Prior research indicates that high levels of PFAS are associated with a variety of adverse health outcomes, including an increased risk of cancer. Reports indicate that mean blood serum levels of perfluorooctanoic acid (PFOA), one type of PFAS, in residents of the exposed community are more than 2 times greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…A complete case ascertainment of thyroid cancer incidence in residents of the communities surrounding the facility in the C8 Study did not find elevated risk based on residence in PFOA‐contaminated water districts (n = 40 exposed cases) or based on estimated PFOA serum levels (n = 15 exposed cases) 23 . A recent ecologic study in Merrimack, New Hampshire observed higher rates of thyroid cancer compared to national incidence rates (RR = 1.47, 95% CI = 1.12‐1.93) among residents whose public drinking water supplies exceeded the national health advisory limit for PFOA 47 . Important limitations of these existing studies include evaluation of only one PFAS (ie, PFOA) and the small numbers of thyroid cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…A complete case ascertainment of thyroid cancer incidence in residents of the communities surrounding the facility in the C8 Study did not find elevated risk based on residence in PFOA‐contaminated water districts (n = 40 exposed cases) or based on estimated PFOA serum levels (n = 15 exposed cases) 23 . A recent ecologic study in Merrimack, New Hampshire observed higher rates of thyroid cancer compared to national incidence rates (RR = 1.47, 95% CI = 1.12‐1.93) among residents whose public drinking water supplies exceeded the national health advisory limit for PFOA 47 . Important limitations of these existing studies include evaluation of only one PFAS (ie, PFOA) and the small numbers of thyroid cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating indicating that PFAS could potentially cause harmful renal, hepatic, immunotoxic, reproductive, and endocrine disrupting effects [6,[12][13][14][15]. PFAS are probably also carcinogenic [3,5,[16][17][18][19][20][21] and possibly induce neurobehavioral and developmental effects [15]. There is some evidence indicating that in early life phases (in utero, childhood) humans might be more sensitive to adverse health effects of PFAS [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence linking exposure to a range of adverse outcomes including renal, hepatic, immunotoxic, reproductive, and endocrine disrupting effects [11][12][13][14][15]. PFAS have carcinogenic properties [6,[16][17][18][19][20][21] and possibly induce neurobehavioral and developmental effects [14]. There is concern that fetal and childhood periods are sensitive exposure windows for adverse health outcomes of PFAS [14,22].…”
Section: Introductionmentioning
confidence: 99%